INVARIANSI PENGUKURAN GENDER SOCIAL MEDIA ENGAGEMENT SCALES FOR ADOLESCENT (SMES-A) VERSI INDONESIA - Rahimmatussalisa, Rahimmatussalisa; Anwar, Anwar; Putri, Mufit Nur Azizah Kusuma (Universitas Muhammadiyah Gresik, 2024)
Background: Social Media Engagement Scales for Adolescent (SMES-A) is ameasurement tool that measures adolescents' engagement in using social mediaconsisting of 11 items with three dimensions, namely cognitive engagement,affective engagement, and behavioral engagement. Objective: This study aimsto conduct a confirmatory factor analysis and test the gender measurementinvariance of the Indonesian version of the SMES-A in order to produce a scalethat has good psychometric characteristics. Method: This study was conductedon the criteria of subjects aged 11-21 years totaling 851 using ConfirmatoryFactor Analyses (CFA) statistical procedures first and then continued withmeasurement invariance. Result: Based on the results of Confirmatory FactorAnalyses (CFA) shows that the factor structure of the Indonesian version of theSMES-A with three factors fits the data and there is gender measurementinvariance. Conclusion: The Indonesian version of the SMES-A measurementtool does not have measurement bias based on gender group differences.